CHOICE OF TREATMENT TACTICS FOR PATIENTS WITH CHRONIC DISEASES OF THE NOSE AND SIDE PANELS AND DACRIOCYSTITIS BY ENDOSCOPIC SURGERY - Burkhanov , Ulugbek (Medical science of Uzbekistan, 2024)
Tear separation is a fairly significant group among all eye diseases and is distinguished by the fact that it occupies a high place in the structure of diseases. According to a number of authors, 8-25.6% of outpatients suffer from lacrimation. In this article, the practice of surgical removal of rhinosinusitis passing through the side cavities of the nose under the endoscope in patients with dacryocystitis is given.